The relationship between nurses’ speaking up about patient safety and nursing work environment in Saudi Arabia: A cross-sectional study - Albalawi, Rawan; Gheith, Nirvana Abdelrahman; Felemban, Ebaa (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Despite nurses’ proximity to patient care, many remain reluctant to voice safety concerns. A significant gap exists in understanding how the professional work environment influences these behaviors within the Saudi Arabian context, where specific cultural and hierarchical norms may impact communication. Objective: This study examined the relationship between nurses’ speaking up regarding patient safety and the nursing work environment in Saudi Arabia. Methods: A cross-sectional descriptive correlational design was used. Data were collected from 270 nurses between August and September 2024 using the Speaking Up About Patient Safety Questionnaire (SUPS-Q) and the Practice Environment Scale of the Nursing Work Index (PES-NWI). Statistical analyses were conducted using SPSS version 28, including descriptive statistics, Spearman’s rank correlation, and ANCOVA. Results: The nursing work environment showed a significant correlation with the speak-up climate. Weak but statistically significant negative correlations were found between perceived concerns and nurse participation (r = -0.210, p = 0.001), quality foundations (r = -0.155, p = 0.011), staffing adequacy (r = -0.184, p = 0.002), and nurse–physician relations (r = -0.156, p = 0.010). Withholding voice also negatively correlated with quality foundations (r = -0.149, p = 0.014) and nurse–physician relations (r = -0.138, p = 0.023). Psychological safety and an encouraging environment showed strong positive correlations with all work environment dimensions (p < 0.001). ANCOVA indicated that education level significantly predicted speaking up (p = 0.042), and experience influenced perceptions of the work environment (p = 0.002), while age and nationality were not significant. Conclusion: Strengthening the work environment is a clinical necessity for safety. Organizations should prioritize “Just Culture” initiatives, systemic learning, and visible responses to raised concerns. Practice protocols should include “safe zones” for voicing concerns away from patients. Professional development must focus on communication skills for addressing high-authority figures. Finally, adequate staffing is essential to empower nurses to prioritize safety advocacy over basic tasks.